Sanksi Adat Pernikahan Sedarah (Perspektif Hukum Adat Minangkabau) - Syarafuddin, Muhsan; Oktaviani, Witia; Jauhar, Ghufran (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: The purpose of this study is to find the implications of customary law for the imposition of severe sanctions on consanguineous marriages in the Minangkabau customary view in Kapur IX District, Lima Puluh Kota Regency. This study uses a type of field research with a qualitative approach. The findings in this study are that consanguineous marriages occur because of differences in views of the Minangkabau customary system using a matrilineal system, so that blood relations from the same mother are stronger than blood relations from the same father, however, consanguineous marriages are recognized as valid by the customary community but are not accepted by custom. The settlement efforts are carried out by summoning, gathering and deliberation so that there is a joint consensus to impose customary sanctions for violations of customary law. Furthermore, customary sanctions are based on the consideration of the couple who reject the customary warning from the customary leader, then personal sanctions are imposed, namely the expulsion of the husband and wife from the village and social sanctions in the form of ostracizing the family from the customary community.Keywords: customary sanction; Minangkabau customary; consanguineous marriage. Abstrak: Tujuan dari penelitian ini adalah untuk menemukan implikasi hukum adat terhadap penjatuhan sanksi berat pada perkawinan sedarah dalam pandangan adat Minangkabau di Kecamatan Kapur IX Kabupaten Lima Puluh Kota. Penelitian ini menggunakan jenis penelitian lapangan (field research) dengan pendekatan kualitatif. Temuan dalam penelitian ini adalah perkawinan sedarah terjadi karena adanya perbedaan pandangan sistem adat Minangkabau yang menggunakan sistem matrilineal, sehingga hubungan darah dari ibu yang sama lebih kuat dibandingkan dengan hubungan darah dari ayah yang sama, meskipun demikian perkawinan sedarah diakui keabsahannya oleh masyarakat adat namun tidak diterima oleh adat. Upaya penyelesaiannya dilakukan dengan cara pemanggilan, pengumpulan dan musyawarah sehingga terjadi konsensus bersama untuk menjatuhkan sanksi adat atas pelanggaran hukum adat. Selanjutnya, sanksi adat didasarkan pada pertimbangan pasangan yang menolak teguran adat dari pemangku adat, maka dijatuhkan sanksi personal yaitu pengusiran suami istri tersebut dari kampung dan sanksi sosial berupa pengucilan keluarga tersebut dari masyarakat adat.Kata kunci: Sanksi Adat; Adat Minangkabau; Pernikahan Sedarah